DETERMINANTS OF CAREGIVER’S KNOWLEDGE IN CARING AND CONDUCTING PHYSICAL EXERCISE ON STROKE PATIENT - Akbar Harisa; Yodang Yodang; Fajar Husodo; Rachmat Fajar; Marhamah Putri Rahmatullah (Jurnal Endurance, 2025)
Family therapy is a form of group therapy where the main issue is the relationship between the patient and their family members. Families who care for family members affected by the disease are referred to as caregivers. This study aims to determine the analysis of Family Based Therapy Development for Stroke Patients with Psycho-Neuro-Muscular Disorders at Home through Family Empowerment as Caregivers.. The research design used was One-Group Pretest-Post test Design research. The population of this study is a family who acts as a caregiver where one of the family members suffers a stroke who lives in the working area of the Puskesmas Tamalanrea, Makassar City. The results of this study found that there was an influence between the provision of ROM intervention on patient skills with a p-value <0.05 (0.025). The results of the signed wilcoxon test of cognitive-behavior therapy (CBT) obtained a p-value of 0.174 so it can be concluded that there is no average difference in skills between the first and second CBT interventions. Conclusion: knowledge and skills are things that are needed by caregivers in caring for families with stroke. Therefore, efforts are needed from various parties, especially the Puskesmas in helping patients in the stroke recovery process in the Puskesmas Tamalanrea working area, Makassar City.